2001
DOI: 10.1002/ajp.1010
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of lion tamarins (Leontopithecusspp) based on interphotoreceptor retinol binding protein intron sequences

Abstract: The evolutionary relationships of the lion tamarins (Leontopithecus) were investigated using nuclear interphotoreceptor retinol binding protein (IRBP) intron sequences. Phylogenetic reconstructions strongly support the monophyly of the genus, and a sister relationship between the golden lion tamarin, Leontopithecus rosalia, and the black lion tamarin, L. chrysopygus, to the exclusion of the golden-headed lion tamarin, L. chrysomelas. The most parsimonious evolutionary reconstruction suggests that the ancestral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
7
18
2
Order By: Relevance
“…This current understanding of the genetics of pigmentation, along with the results presented here and by other genus-level studies [58,59], sharply contrasts with the irreversible pathways proposed by the metachromism hypothesis. Although the agouti banding pattern seems to be the primitive condition for mammalian hair [2], and the evolutionary sequence of colour changes fits the metrachromism model in the Neotropical genus Saguinus [60], this non-adaptive hypothesis does not constitute a general principle for Neotropical primates.…”
Section: Discussioncontrasting
confidence: 97%
“…This current understanding of the genetics of pigmentation, along with the results presented here and by other genus-level studies [58,59], sharply contrasts with the irreversible pathways proposed by the metachromism hypothesis. Although the agouti banding pattern seems to be the primitive condition for mammalian hair [2], and the evolutionary sequence of colour changes fits the metrachromism model in the Neotropical genus Saguinus [60], this non-adaptive hypothesis does not constitute a general principle for Neotropical primates.…”
Section: Discussioncontrasting
confidence: 97%
“…Phylogenetic analysis under Dollo parsimony (assuming that informative characters -in this case restriction sites -are more frequently lost than gained because nucleotide substitutions alter base pair sequences at recognition sites) showed a closer relationship between L. chrysomelas and L. chrysopygus, sustained by a shared gain of one HindIII and one EcoRI site. This arrangement was in agreement with the distance-based allozyme data of Forman et al (1986), but contradictory to both the distancebased reconstruction derived from cytochrome b sequence data Moreira and Seuá nez, 1999) and nuclear IRBP sequences (Mundy and Kelly, 2001). …”
Section: Callitrichine Radiation: Molecular and Cytogenetic Datasupporting
confidence: 70%
“…Sequence analyses of ß 2 m in several individuals of three Leontopithecus species failed to show interspecific or intraspecific differences, precluding resolution of their phylogenetic relationship (Canavez et al, 1998). Mundy and Kelly (2001), however, using sequence data from intron 1 of the IRBP gene, proposed a clear sister-taxon relationship between golden lion tamarins (L. rosalia) and black lion tamarins (L. chrysopygus).…”
Section: Callitrichine Radiation: Molecular and Cytogenetic Datamentioning
confidence: 99%
“…110 However, there are clear examples where reconstructions of coat color evolution from phylogenetic studies do not support metachromism. 26,111 Moreover, the genetic studies of color changes in many mammals 105 have shown that point mutations can lead to dramatic changes in the distribution of the two types of melanin (eumelanin and pheomelanin, Box 1). Thus, it is hard to reconcile what we now know about the genetics of pigmentation with the irreversible pathways following initial saturation proposed by metachromism.…”
Section: Box 3 Metachromismmentioning
confidence: 99%